Laparoscopic Cholecystectomy at the Korle Bu Teaching Hospital, Accra, Ghana - Clegg-Lamptey, J.N.A.; Amponsah, G. (West African Journal of Medicine, 2010)
BACKGROUND: Laparoscopic cholecystectomy (LC) the preferred treatment for gallstones was not available in Ghana until 2005. OBJECTIVE: To report experience from Ghana of laparoscopic cholecystectomy in the treatment of galestones. METHODS: In a prospective study of patients with gallstones, information was obtained on demography, duration of various stages of the operation, analgesia and complication of patients with gallstones. All patients had general anaesthesia using endotracheal intubation, muscle relaxant and intermittent positive pressure ventilation. A standard four-trocar technique and maximum pneumoperitoneum pressure of 14mmHg were maintained during surgery. RESULTS: There were 50 women and two men aged 17-72 years (mean 44.2 years). All had symptomatic gallstones treated by interval LC. The main indications were biliary colic 23(44%) and previous cholecystitis 15(29%). There were scars from previous abdominal surgery in 22 (42%), mainly pfannenstiel. The Verres needle was used to obtain pneumoperitoneum in 40 (77%). Only one patient (1.9%) had the operation converted to open cholecystectomy. Most patients, 47/51 (92%), were discharged in 24 hours. The mean durations of various stages were: anaesthesia (110 minutes), pneumo-peritoneum (67.5 minutes) and reverse trendelenburg (47.8 minutes). The mean operating time reduced from 81 to 68 minutes in the last 20 patients. Complications were sore throat 11(21.6%), infection of the umbilical wound 3(5.9%), right shoulder tip pain (3; 5.9%) and bile leak 1(2%). There was no peri-operative mortality. CONCLUSION: Elective laparoscopic cholecystectomy can be performed with good results in patients with symptomatic gallstones in Accra.
An initial report [Cholécystectomie laparoscopique à l'Hôpital universitaire de Korle Bu, Accra, Ghana: Un premier rapport]
Keywords: Gallstones; Ghana; Laparoscopic cholecystectomy; Treatment outcome